Cytochrome P450 1A1 is essential for the microbial metabolite, Urolithin A-mediated protection against colitis - Ghosh, Sweta; Moorthy, Bhagavatula; Haribabu, Bodduluri; Jala, Venkatakrishna Rao (Frontiers in Immunology, 2022)
Background: Cytochrome P450 Family 1 Subfamily A Member 1 (CYP1A1) pathway, which is regulated by aryl hydrocarbon receptor (AhR) plays an important role in chemical carcinogenesis and xenobiotic metabolism. Recently, we demonstrated that the microbial metabolite Urolithin A (UroA) mitigates colitis through its gut barrier protective and anti-inflammatory activities in an AhR-dependent manner. Here, we explored role of CYP1A1 in UroA-mediated gut barrier and immune functions in regulation of inflammatory bowel disease (IBD). Methods: To determine the role of CYP1A1 in UroA-mediated protectives activities against colitis, we subjected C57BL/6 mice and Cyp1a1-/- mice to dextran sodium sulphate (DSS)-induced acute colitis model. The phenotypes of the mice were characterized by determining loss of body weight, intestinal permeability, systemic and colonic inflammation. Further, we evaluated the impact of UroA on regulation of immune cell populations by flow cytometry and confocal imaging using both in vivo and ex vivo model systems. Results: UroA treatment mitigated DSS-induced acute colitis in the wildtype mice. However, UroA-failed to protect Cyp1a1-/- mice against colitis, as evident from non-recovery of body weight loss, shortened colon lengths and colon weight/length ratios. Further, UroA failed to reduce DSS-induced inflammation, intestinal permeability and upregulate tight junction proteins in Cyp1a1-/- mice. Interestingly, UroA induced the expansion of T-reg cells in a CYP1A1-dependent manner both in vivo and ex vivo models. Conclusion: Our results suggest that CYP1A1 expression is essential for UroA-mediated enhanced gut barrier functions and protective activities against colitis. We postulate that CYP1A1 plays critical and yet unknown functions beyond xenobiotic metabolism in the regulation of gut epithelial integrity and immune systems to maintain gut homeostasis in IBD pathogenesis.